Antimicrobial Activity of Encapsulated Mexican Oregano (Lippia berlandieri Schauer) Essential Oil Applied on Bagels - Salgado-Nava, Aída Araceli; Hernández-Nava, Ruth; López-Malo, Aurelio; Jiménez-Munguía, María Teresa (Frontiers in Sustainable Food Systems, 2020)
Several in vitro studies of Mexican oregano essential oil (MOEO) have demonstrated its effectiveness as an antimicrobial. On the other hand, the encapsulation technique of emulsification could be used to mask the intense flavor of MOEO, protect it from physico-chemical degradation, and release gradually its antimicrobial components. In the present study, emulsions were elaborated with two encapsulating agents, pectin or Arabic gum, with five concentrations of MOEO (5, 7.5, 10 or 15% w/w). Emulsions were characterized by density, viscosity, particle size distribution, creaming index and peroxide index. Emulsions were applied, in a 3:1 ratio, on the surface of two formulations of bagel, one with wheat flour (BW) and another, with wheat flour and oats (BWO). Bagels were characterized by water activity, moisture content and hardness. The antimicrobial activity of MOEO encapsulated by emulsification on Penicillium expansum on the surface of the bagels was determined. In addition, a sensory analysis of the bagels was carried out using a hedonic scale. All physico-chemical properties of the emulsions had a significant difference (p < 0.05), because of the encapsulating agent used (pectin or Arabic gum). Emulsions stabilized with Arabic gum were more stable over time than the ones with pectin. The application of the emulsions on the surface of the bagels did not showed statistical difference (p > 0.05) in the physico-chemical properties of the breads. The growth of P. expansum was delayed for up to five or six days in bagels with wheat flour and Arabic gum as encapsulating agent. Both systems, BW and BWO, atomized with MOEO emulsions at high concentrations (MOEO 15% w/w) were well accepted by the panel of judges when these were evaluated on day 0 (freshly baked bread), but not after six days of their elaboration.